1983
DOI: 10.1113/jphysiol.1983.sp014536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetanus toxin on the excitatory and the inhibitory post‐synaptic potentials in the cat motoneurone.

Abstract: smaller than those in control animals (15 + 1.0 mV versus 5-6 + 2-7 mV; t test, P < 0-001).3. Heteronymous Ia e.p.s.p.s produced by stimulation ofthe lateral gastrocnemiussoleus nerve 5 days after toxin injection were also significantly smaller than those in control animals (0-6 ± 0-6 mV versus 2-5 + 15 mV; P < 0-001). However, these heteronymous Ia e.p.s.p.s remained normal when the lateral gastrocnemius-soleus nerve was ligated and sectioned at the entry to those muscles just before the toxin injection.4. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 36 publications
3
11
1
Order By: Relevance
“…Release of GABA recovered with seizure remission. Tetanus toxin may affect other transmitter systems, however, at least at the higher doses used in acute studies (Duchen and Tonge, 1973;Albus and Habermann, 1983;Kanda and Takano, 1983;Bevan and Wendon, 1984;Penner et al, 1986). The specificity of the low dose of toxin used in the chronic model remains to be tested, but electro-physiologic recordings clearly show that excitatory synaptic transmission remains effective in vitro in hippocampal slices from such animals (Jefferys, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Release of GABA recovered with seizure remission. Tetanus toxin may affect other transmitter systems, however, at least at the higher doses used in acute studies (Duchen and Tonge, 1973;Albus and Habermann, 1983;Kanda and Takano, 1983;Bevan and Wendon, 1984;Penner et al, 1986). The specificity of the low dose of toxin used in the chronic model remains to be tested, but electro-physiologic recordings clearly show that excitatory synaptic transmission remains effective in vitro in hippocampal slices from such animals (Jefferys, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly the toxin can block synaptic transmission peripherally for several weeks and it has been shown at the skeletal neuromuscular junction that recovery of synaptic function depends on the growth of new terminals rather than the repair of old ones (Duchen, 1973;Duchen & Tonge, 1973). In the central nervous system, the direct effect of the toxin appears to be generally excitatory, through a presynaptic block ofinhibitory transmission (see Mellanby & Green, 1980 Collingridge, Thompson, Davies & Mellanby, 1981;Wellhoner, 1982), although it can also block synaptic excitation (Kanda & Takano, 1983). Even if the block of inhibition were sufficiently long-lasting it would be in the wrong sense to account directly for the depression of CA3 excitability reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that synaptic input plays a key role in determining a pattern of recruitment since the high dose led to a recruitment pattern that shifts and expands in range with respect to control. TeNT not only blocks synaptic inhibition, but also excitation, as shown both in vivo (Curtis et al 1976;Kanda and Takano 1983) and in vitro (Gobbi et al 1993). …”
Section: Synaptic Organization As Factor That Influences Recruitmentmentioning
confidence: 94%
“…In summary, we conclude that a recruitment order based solely in size-related factors does not produce a rule to rank motoneurons as a function of neuronal sensitivity. The use of TeNT does not modify this view since it has been shown that TeNT does not alter the excitability of either spinal (Kanda and Takano 1983;Wiegand and Wellhöner 1979), cranial motoneurons in vivo (González-Forero et al 2002a), or cultured neurons (Dimpfel 1979).…”
Section: Intrinsic Correlates To Recruitment Ordermentioning
confidence: 99%